Family History in the Assessment of Risk for Common Complex Diseases: Current State of Evidence - Hasanaj, Qendresa (Université d'Ottawa / University of Ottawa, 2012)
Family history (FH) is a risk factor for many diseases. Disease guidelines often include family history as important in assessing chronic disease risks, but the empirical evidence base to inform the routine use of family history in primary care in practice appears largely lacking. An environmental scan of how family history is represented in prevention guidelines for five conditions showed that, while family history is often included in guidelines, there is variation in the definition used, recommendation given and evidence cited. A dataset on cardiovascular health in women was analyzed to examine whether family history offers useful discrimination value above standard risk factors. Regression results showed that family history is an independent risk predictor for coronary heart disease which improves discrimination beyond classical clinical factors. However, the absolute amount of discriminatory ability alone or with other factors is moderate at best, raising issues regarding clinical utility.
Keywords: risk assessment; family history; chronic diseases; coronary heart disease; clinical discrimination factors